Women’s Language in “Bring It On” Movie - Made Dwi Susanti, Valeria; Istri Aryani, I Gusti Agung (Humanis; Vol 22 No 3 (2018), 2018)
The title of this study is Women’s Language in the Movie “Bring It On” . This study aims at identifying and analyzing type of women’s linguistic features and functionsapplied by women characters in the movie. This movie entitled Bring It On directed by Peyton Reed and written by Jessica Bendinger was chosen as the data source of this study. The data of this study was obtained by watching and listening to the movie to find the women’s linguistic features used by the women characters in the movie. The collected data were analyzed qualitatively in order to give clear description. There were nine features found in the conversation of women characters of the movie, such as: lexical hedges or filler (e.g. such as well, you know, I think , I mean) , tag question, rising intonation on declarative, “empty” adjective, intensifier (e.g. just , so ), hypercorrect grammar, “superpolite” forms (e.g. thank you) , precise color, and avoidance of strong swear word. In addition, the function found in this study as of: lexical hedges that showed women uncertain about what they are saying or cannot vouch of the accuracy of their statement; using tag question to make small talk or trying to elicit conversation from the addressee because the speaker needs confirmation from the addressee; using rising intonation is to seek for confirmation; using empty adjective is to show the speaker’s approbation or admiration for something; using precise color term is related to women’s specific interest and to show that they are good in their field; using intensifier is to emphasize and strengthen the statement; using hypercorrect grammar is to show politeness to the addressee; using super polite form is to show their gratitude to the addressee; using avoiding strong swear word is to show how strongly women show their feeling about something.